2003
DOI: 10.1111/j.1547-5069.2003.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Perceptions of Self‐Worth in Preadolescents Diagnosed with ADHD

Abstract: Participation in a school-based, nurse-led support group was positively associated with perception of self-worth in preadolescents diagnosed with ADD or ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 15 publications
0
32
1
4
Order By: Relevance
“…Therefore, the nurse should be responsive to all family members and refer to treatment when necessary. [15][16][17][18] According to the American Psychiatric Association (APA) that five evidence-based treatments exist for children with ADHD in the form of stimulant medication lines, behavioral parent training, social skills training, summer treatment programs and behavioral classroom interventions. [10] Although, drug therapy is the most common method for treating ADHD and stimulant medicines are fairly effective for many children, but 42% of children don't response to medicines and increase behavioral problems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the nurse should be responsive to all family members and refer to treatment when necessary. [15][16][17][18] According to the American Psychiatric Association (APA) that five evidence-based treatments exist for children with ADHD in the form of stimulant medication lines, behavioral parent training, social skills training, summer treatment programs and behavioral classroom interventions. [10] Although, drug therapy is the most common method for treating ADHD and stimulant medicines are fairly effective for many children, but 42% of children don't response to medicines and increase behavioral problems.…”
Section: Introductionmentioning
confidence: 99%
“…[1,3,19] Researches have shown that play therapy can manage all issues related to self-esteem & self-concept, adapting to new situations as a new school, uncharacteristic behavior as withdrawn, being aggressive and destructive, keeping friends, symptomatic behavior such as stomach ache, bed-wetting, headache, depression, anxiousness, ADHD, psychological trauma from birth of a sibling, parent divorce or death of a parent, in addition to nightmares, fear and anxiety. [1,3,15,20] Pediatric and school nurses, psychologists in addition to play therapists work with children of all ages in a trusting and safe environment to help shift perspectives of difficult experiences and increase confidence and self-esteem. They may work as part of a team or individually, and may ask a referral for additional professional support as part of therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…141,[189][190][191][192][193][194][195][196][197][198][199][200][201][202] Forty-seven contained data suitable for meta-analyses; seven studies 141,162,180,186,191,192,198 included empirical data that could not be meta-analysed and that were, therefore, synthesised narratively. Three studies 104,143,185 included some data that were meta-analysed and some data that were synthesised narratively.…”
Section: Study and Participant Information: Descriptive Statisticsmentioning
confidence: 99%
“…144 For seven studies where the relevant empirical data were not reported or available from the study authors, only narrative synthesis was conducted. 141,162,180,186,191,192,198 All data were extracted by MR and checked by DM with all disagreements resolved successfully through discussion.…”
Section: Statistical Informationmentioning
confidence: 99%